PENERAPANA PENDEKATAN KONTEKSTUAL untuk MENINGKATKAN MINAT BELAJAR SENI BUDAYA DI SMPN 2 GALESONG SELATAN - Imamatul Islamyah; Erni Rosida; Nasir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of cultural arts learning in addressing the low learning interest of students, which is influenced by limited facilities, teacher readiness, and student readiness in the teaching and learning process at SMP Negeri 2 Galesong Selatan, particularly in grade VIII. These conditions affect students’ low engagement and learning outcomes that have not yet reached optimal standards. To overcome these issues, the Contextual Teaching and Learning (CTL) approach is applied, emphasizing the connection between learning materials and students’ real-life contexts so that learning becomes more relevant and meaningful.The research method used is Classroom Action Research (CAR), conducted in three cycles, each consisting of planning, implementation, observation, and reflection stages. The application of CTL is supported by the use of popular culture–based media such as videos, animations, and music to create an engaging, interactive, and enjoyable learning atmosphere.The results of the study indicate a significant increase in students’ emotional and intellectual engagement. In addition, the average learning outcomes consistently improved in each cycle, reaching the “excellent” category in the third cycle. Thus, the CTL approach is proven effective in increasing students’ interest and learning outcomes in cultural arts, even when the school faces limitations in learning facilities.